Bermain di Pelataran Doa: Konsep Diri Pengemis Anak di Wisata Religi Kubah Basirih Kota Banjarmasin - Utami, Diyah Yasmina; Hidayah, Sri (Huma: Jurnal Sosiologi, 2025)
Children who should be focusing on their education often neglect their obligations by skipping school to play and beg around Kubah Basirih. This research aims to explore the self-concept of child beggars in the Religious Tourism of Kubah Basirih, Banjarmasin, using phenomenological approach and George Herbert Mead's symbolic interactionism theory. This qualitative study involves data collection through observation, semi-structured interviews, and documentation from seven child beggar informants. The research process includes data collection, data reduction, data presentation, and conclusion drawing. Findings indicate that driving factors for children begging include personal desire for money, peer influence, and parental requests. Begging activities help them develop communication skills, observational skills, and understanding of verbal and non-verbal symbols. Social interactions with visitors shape their self-perception, often at the expense of formal education. The study also reveals that child beggars at Kubah Basirih prioritize playing and socializing with peers over simply earning money from begging. They enjoy companionship and support from peers, fulfilling their desire as children to experience happiness. Consequently, this often leads them to neglect formal education, which should be their primary focus. These findings underscore the importance of understanding how self-concept forms not only from subjective experiences but also through self-reflection and interaction with the environment.